Removal of Lead Ions From Aqueous Solutions Using Melamine-Modified Nano Graphene Oxide - Nazanin Parsa; Hassan Rezai (Avicenna Journal of Environmental Health Engineering, 2020)
Today, due to the industrialization of societies, the existence of heavy metals has created many problems for humans, other organisms, and the environment. Lead (Pb) is highly toxic and the second most commonly used metal. The aim of this study was to evaluate the efficiency of melamine-modified nanographene oxide in the removal of Pb from aqueous media. To increase the efficiency of graphene oxide, it was mechanically converted to nano graphene oxide and melamine (4, 2 and 6-triazine, 3, 1 and 5 triamine). Experiments were performed at pH value of 3-8, temperature of 15-50°C, Pb concentration of 5-200 mg/g, adsorbent dose of 0.01-0.06 g, and contact time of 15- 150 minutes. The mechanism of the adsorption process was investigated using two Langmuir and Freundlich isotherm models, pseudo-first order and pseudo-second order kinetic equations, and thermodynamic equations. The results showed that the adsorption rate corresponds to the Freundlich isotherm model and pseudo-second order kinetic equation. Thermodynamic studies also showed that the adsorption process is associated with increasing irregularities and it is endothermic. In constant conditions (pH of 6, contact time of 60 minutes, ambient temperature of 22°C, Pb concentration of 20 mg/L, and adsorbent dose of 0.01 g), the adsorption capacity was 191.65 mg/g. The highest adsorption occurs at the concentration of 5 mg/L and the highest adsorption capacity and removal percentage was observed at a concentration of 200 mg/L, which were 1896.3 mg/g and 98.8%, respectively. Due to the high adsorption capacity, the adsorbent was able to remove lead from the contaminated environment.